A Study of Procalcitonin as Biomarker in Sepsis Patients Admitted in Super Speciality Hospital - Prabhakar, Pranav Kumar (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: Sepsis, a systemic inflammation, mainly originated due to infectious viral, fungal, or parasitic infections. No long-term data are available which compare the procalcitonin (PCT) levels and C-reactive protein (CRP) levels in different emergency conditions as well as differentiating the PCT levels in males and females in sepsis or other related condition. The main objective of this study was to evaluate PCT, a reliable biomarker, and to compare the different parameters for the diagnosis of sepsis, severe sepsis, and septic shock conditions. Materials and Methods: For this study, the samples of 74 patients were taken which were admitted in Intensive Care Unit (ICU) in the Max Hospital, Mohali. All the candidates fall in the age group of 05–70 years. The parameters which were used for the diagnosis and differentiating the sepsis conditions were PCT levels, CRP levels, and total leukocyte count levels. The total number of 74 patients was grouped into different groups on the basis of their gender, age and P-value. After a period of 16 weeks, subjects from different groups had great difference in their PCT values in the sepsis condition. Results and Discussion: The Gram-negative bacteria are one of the most common causative agents associated with sepsis condition which was 54.3%, whereas remaining 45.7% was other Gram-positive bacteria, fungi, and yeast. From the study, it was appeared that the prevalence of sepsis condition is found to be more prominent in males as compared to females. It will be concluded that severity of sepsis increases as serum PCT increases and similarly mortality also increased. Conclusion: Sepsis is the most common cause of morbidity and mortality in ICU. Due to its low specificity of CRP in the sepsis condition and unable to differentiate between the severities of the infection, we need to look for another biomarker. Thus, PCT is more promising reliable biomarker for the diagnosis of sepsis and start to effective antibiotic and reducing the mortality.